Artificial resting sites: An alternative sampling method for adult mosquitoes. Issue 2 (25th November 2021) - Jaworski, Linda; Sauer, Felix; Jansen, Stephanie; Tannich, Egbert; Schmidt‐Chanasit, Jonas; Kiel, Ellen; Lühken, Renke
Abstract: Mosquito collections are commonly conducted with baited traps predominantly attracting host‐seeking females. In contrast, resting sites are generally colonized by a broader range of the mosquito population, including a higher proportion of males and blood‐engorged females. This study evaluates the sampling success of different artificial resting sites, attached to a deciduous or coniferous tree at different heights. As standard sampling method, carbon dioxide‐baited Biogents Sentinel traps (BG traps) were operated in parallel. BG traps caught a higher number of specimens compared to the resting sites. However, the proportion of blood‐engorged females and males was higher in resting sites. More Culiseta spp. specimens were collected in resting sites compared to BG traps, but less Aedes spp. specimens. In general, fewer specimens and species were recorded in small resting sites and at top height level compared to medium or large resting sites at medium or ground level. The proportion of males was highest at the ground, while the proportion of engorged females was highest at medium and top level. Due to the higher proportion of blood‐engorged females, artificial resting sites are especially useful for studies of host‐feeding patterns or xenosurveillance. Low costs and efforts allow a cost‐effective increase of the number of resting sites per sampling site to collect more mosquitoes. Abstract : Pop‐up garden bags as artificial resting sites should have a large size and positioned close to the ground in order to sample high numbers of mosquito species and specimens. Artificial resting site collections provide fewer specimens than carbon dioxide‐baited traps with a lower prevalence of Aedes species. With a higher number of blood‐engorged females at medium height level, this trapping method is particularly suitable for studies on host‐feeding patterns or xenosurveillance.